Comportamento de consumo de corredores de rua: uma abordagem baseada na teoria da prática - Costa, Américo Pierangeli (2016)
Road running can be understood as one of the simpler forms of physical exercise. Its long history has demonstrated a richness of variations in the format of its practice. Marketing and consumer behavior studies have been conducted in empirical fields, which allows the understanding of complex phenomena relevant to social life. The practice theory, proposed as a contemporary alternative of understanding consumption phenomena, adds new presuppositions that guide consumption understanding as base of the routines of individuals. This research had the objective of understanding the consumer behavior of street runners, using as approach the practice theory. In this study, we proposed the use of practice elements as analysis categories for the collected data. Data analysis was used on the data collected from three sources: specialized magazines, focus groups and non-participatory observation. The practice elements as analysis categories demonstrate good applicability. The consumption of the street runners was described in 12 categories: “Knowledge, understanding and learning”; “know-how”; “mental activities”; “emotional states”; “motivational knowledge”; “engagement”; “hierarchies”; “intersections”; “body activities”; “representations”; “objects, appropriations and uses” and “trajectory”. The road running are demonstrated as a relevant part of the practitioner’s routines. The consumption of the street runners was described as a moment of the practice, and, therefore, a moment of its elements. The consumption decisions seem to receive strong influence from the practice elements. Due to the representativeness of the street runs in the routines of the practitioners, the consumption seems to occur by negotiations with other practices. The remaining practices can occur with or complement the elements of the street running practice.